177k views
4 votes
I need help please and thank you

I need help please and thank you-example-1
User Kousei
by
6.6k points

1 Answer

5 votes

Answer:


\large\boxed{(8x-17)/(4x^2-36)}

Explanation:


(7)/(4x^2-36)+(4)/(2x+6)\\\\=(7)/(2^2x^2-6^2)+(4)/(2x+6)\\\\=(7)/((2x)^2-6^2)+(4)/(2x+6)\qquad\text{use}\ (a+b)(a-b)=a^2-b^2\\\\=(7)/((2x-6)(2x+6))+(4)/(2x+6)\\\\\text{We must have the same denominator.}\\\\\text{LCD is}\ (2x-6)(2x+6)


=(7)/((2x-6)(2x+6))+(4(2x-6))/((2x+6)(2x-6))\\\\=(7+4(2x-6))/(4x^2-36)\qquad\text{use the distributive property}\\\\=(7+(4)(2x)+(4)(-6))/(4x^2-36)\\\\=(7+8x-24)/(4x^2-36)\\\\=(8x+(7-24))/(4x^2-36)\\\\=(8x-17)/(4x^2-36)

User Rouge
by
5.1k points